Application of a Heat- and Steam-Generating Sheet Increases Peripheral Blood Flow and Induces Parasympathetic Predominance. (22nd March 2011) - Nagashima, Yoshinao; Igaki, Michihito; Suzuki, Atsushi; Tsuchiya, Shuichi; Yamazaki, Yoshimi; Hishinuma, Michiko; Oh-ishi, Sachiko; Majima, Masataka
Abstract : To promote the practical application of a Japanese traditional medical treatment, such as hot compresses, we developed a plaster-type warming device consisting of a heat- and steam-generating sheet (HSG sheet). First, we tested its effects when applied to the anterior abdominal wall or lumbar region of women complaining of a tendency towards constipation. Application of the sheet to either region produced a feeling of comfort in the abdomen, as assessed by a survey of the subjects. The significant increases in the total hemoglobin observed in these regions suggested an increase in peripheral blood flow, and significant increases in the HF component on ECG and in the amplitude of gastric motility suggested parasympathetic predominance. We concluded that application of the HSG sheet improves the peripheral hemodynamics and autonomic regulation, induces a feeling of comfort in the abdomen, and provides a beneficial environment for the improvement of gastrointestinal movements.